Investing activities as the basis for providing employment in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
Activities on the basis of innovation and investment to create a competitive manufacturing and new jobs. Thesustainability of the legal framework of investment activity will result in not only improving the economic status ofsubjects of economic relations, but also to achieve stability in the area of employment.Key words: investment, investment law, investment policy, investment, employment.